TURKISH RETAIL INDUSTRY AND THE RELATIONS WITH ALBANIA - Yarimoglu, Emel Kursunluoglu (European Scientific Journal, ESJ, 2014)
This study showed how the structure of the retail industry has been transformed since 1920s in Turkey by the new retail formats. The Turkish retail industry has been developing since 1980s. It had too many foreign operations and Turkish retailers have begun to enter foreign countries for a long time. Turkish operations in Albania were analysed since Albania has taken too much investments that leading to retail development and Turkey was the thirdlargest foreign direct investor in Albania. The study analysed secondary data about retail industry in Turkey and Albania. It aimed to explain the history of retail industry in Turkey and show the situation of Albania in retail development. The study was original because of the lack of academic research focused on Turkish retailing and Turkish investments in Albania. Future research may be related to the measuring the incentives and obstacles of Turkish investments in Albania with a field study.